Evaluation of the Elements and Characteristics of the Facades of Cultural Heritage Buildings in the Context of Colonial Architecture - Khoudiy Iffiyah (Journal of Social Research, 2026)
This study examines the importance of preserving colonial cultural heritage buildings as part of urban identity and historical continuity. In many developing cities, rapid urbanization and functional changes have threatened the authenticity of heritage buildings, particularly their façades, which serve as the primary visual representation of architectural character. In Indonesia, colonial buildings in urban areas such as Surabaya hold significant historical and aesthetic value, yet face increasing pressure from modernization. Therefore, this research aims to evaluate the elements and characteristics of the façade of the Hagakita Bank Building as a representative colonial heritage structure and to assess how these elements contribute to maintaining its architectural identity. This study employs a qualitative-descriptive approach, utilizing purposive sampling with the Hagakita Bank Building as the primary research object. Data were collected through direct observation, photographic documentation, and literature review. The research instruments included observation sheets and documentation guidelines, while data validity was ensured through triangulation of sources and methods. The results show that façade elements such as form, openings, color, decoration, materials, and texture play a significant role in preserving the colonial architectural identity. These elements not only reflect historical authenticity but also enhance public appreciation of heritage buildings. In conclusion, maintaining the integrity of façade elements is essential for sustainable conservation and for strengthening the cultural identity of urban heritage areas.